Estimates of average energy requirements in Bangladesh: Adult Male Equivalent values for use in analyzing household consumption and expenditure surveys - Waid, Jillian; Gabrysch, Sabine (Data in Brief, 2017)
This dataset contains Adult Male Equivalent (AME) values for use in Bangladesh. These were constructed using prescriptive nutritional constructs adapted to the actual growth and weight pattern seen in Bangladesh. This dataset provides a common base to facilitate for future work with household consumption and expenditure data in Bangladesh while updating the average energy requirements for infants and young children for the WHO 2006 growth standards and 2007 growth reference curves.